Factors associated with knowledge, attitude and practices on fire safety and its prevention among hostel occupants in a higher learning institution - Ahmad AlWaqfi, Ahmad Saeed; Ng, Yee Guan; Lim, Poh Ying; Md Tamrin, Shamsul Bahri (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Failure to prepare students on fire safety and prevention in hostels adequately may result in various losses not limited to life and health but also in terms of properties, intellectual properties, and morale. As practices relates closely to knowledge and attitude, the aim of this study was to investigate the level of their knowledge, attitude and practices (KAP) in fire safety and prevention and its associated factors among hostels occupants in a university. Methods: A cross-sectional study was conducted from March 2020 to October 2020, using online questionnaire with five different sections to obtain respondents’ sociodemographic information, past-experiences and KAP related to fire safety and its prevention. Results: Out of 283 students, the prevalence of having acceptable level of knowledge, positive attitude and good practice were 62.0%, 87.9% and 49.3% respectively. Multiple logistic regression showed that non-Malay respondents were less likely (OR=0.301) to have acceptable knowledge level but those who had past-experiences in fire drill training particularly hands-on in fire drill training have significantly higher odds (OR=5.694; OR=2.353 respectively) of having acceptable knowledge in fire safety and prevention. Respondents who had hands-on in fire drill training was the predictor for positive attitude (OR = 2.285); whereas respondents with total household monthly income RM4,850-RM10,959 has 3.000 higher odds of good practice in fire safety and prevention. Conclusion: It may be worthwhile to explore other approaches in accident prevention besides KAP model (attitude change via knowledge to modify behaviour) in this case, fire safety and its prevention.